2013
DOI: 10.1007/s10286-013-0215-9
|View full text |Cite
|
Sign up to set email alerts
|

Autonomic dysfunction of overweight combined with low muscle mass

Abstract: This study suggests that HRV is reduced in overweight combined with low muscle mass group than overweight and HMM group.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
14
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 27 publications
2
14
0
Order By: Relevance
“…This is supported by a study carried out by Baek et al [34] which shows that SDNN, RMSSD and HF are reduced in individuals with high BMI.…”
Section: Discussionsupporting
confidence: 74%
“…This is supported by a study carried out by Baek et al [34] which shows that SDNN, RMSSD and HF are reduced in individuals with high BMI.…”
Section: Discussionsupporting
confidence: 74%
“…But there is no definite study that showed that isolated grip strength was associated with abnormal HRV. Recent studies showed that muscle mass in obese patients is more likely to be related to HRV (34). Our study also found that lower muscle mass (lower than 25%) was related to HRV (OR, 95%CI; 0.92, 0.89-0.95) in obese but not in healthy individuals.…”
Section: The Relation Between Hrv and Isolated Low Grip Strengthsupporting
confidence: 71%
“…Although many studies have shown changes in HRV in athletes and physically active people 33 , few studies have linked these findings to the composition of muscle mass. Some authors have found that HRV in overweight patients is lower when it is associated with reduced muscle mass 34 , while other authors have shown that anthropometric behavior contributes to changes in the HRV 35 . A small sample of individuals was used because this was considered a pilot study; the sample should be expanded to validate the equations.…”
mentioning
confidence: 99%